Logic detection algorithm for dual logic implementations based on majority cubes - Wang Lunyao; Xia Yinshui; Chen Xiexiong (2010 International Conference on Computer Application and System Modeling (ICCASM 2010), 2010)
Based on the disjointed cubes of the logic functions, a method by searching majority cubes and Hamming distance to detect logic functions suitable for XOR logic implementation is presented. Some special covers of functions which meet the majority cubes will be expressed as a m-dimension cube and other offset cubes. After majority cubes searching, another logic detection method with hamming distance is used to incorporate those products whose hamming distances are 1 or 2. The proposed algorithm is implemented in C and tested on MCNC benchmarks. The experimental results show that the proposed algorithm is efficient compared with published results.